The representation of executed Indonesian migrant workers in The Jakarta Post news articles - Utama, Gina Nanda; Amalia, Rosaria Mita; Yuliawati, Susi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
This study discusses how the representation of executed Indonesian migrant workers in the case of their executions in Saudi Arabia from 2015 to 2018 in The Jakarta Post news articles. This study is analyzed by using Critical Discourse Analysis (CDA) which specifically uses the Social Actor Representation (SAR) theory from van Leeuwen (2008). In analyzing the data, this study is also supported by the theory of levels of analysis from Richardson (2007) to analyze the text producers’ lexical choice and the theory of transitivity from Halliday and Matthiessen (2004) to analyze the role allocation. This study shows that The Jakarta Post represents the executed Indonesian migrant workers negatively. It can be seen from the text producers’ ways to include the executed Indonesian migrant workers in the representation. Moreover, The Jakarta Post also uses the words ‘kill’, ‘knife to death’, ‘stab’ etc. to describe the executed Indonesian migrant workers.